2007
DOI: 10.1086/523042
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the Narrow-Line Seyfert 1 Galaxy Markarian 335 in a Historical Low X-Ray Flux State

Abstract: We report the discovery of the narrow-line Seyfert 1 galaxy Mrk 335 in an extremely low X-ray state. A comparison of Swift observations obtained in 2007 May and June/July with all previous X-ray observations between 1971 and 2006 show the AGN to have diminished in flux by a factor of more than 30, the lowest X-ray flux Mrk 335 has ever been observed in. The Swift observations show an extremely hard X-ray spectrum at energies above 2 keV. Possible interpretations include partial-covering absorption or X-ray ref… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
115
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(127 citation statements)
references
References 44 publications
12
115
0
Order By: Relevance
“…The ∼ 0.9 keV feature was not required in the high-flux spectrum with the normalisation being consistent with zero when a Gaussian profile was included. The emission feature is comparable in flux and energy to that reported by Grupe et al (2007) The residuals to this model portray an absorption-like feature at approximately 7 keV in the low-flux spectrum that could arise from highly ionised iron in a warm absorber. Longinotti et al (2013) modeled the complex absorption seen in the intermediate flux-state of Mrk 335 with a triple-zone warm absorber.…”
Section: Blurred Reflection Fits For the Multi-epoch Spectral Datasupporting
confidence: 75%
See 1 more Smart Citation
“…The ∼ 0.9 keV feature was not required in the high-flux spectrum with the normalisation being consistent with zero when a Gaussian profile was included. The emission feature is comparable in flux and energy to that reported by Grupe et al (2007) The residuals to this model portray an absorption-like feature at approximately 7 keV in the low-flux spectrum that could arise from highly ionised iron in a warm absorber. Longinotti et al (2013) modeled the complex absorption seen in the intermediate flux-state of Mrk 335 with a triple-zone warm absorber.…”
Section: Blurred Reflection Fits For the Multi-epoch Spectral Datasupporting
confidence: 75%
“…The low-flux spectra are identical above 2 keV, but the XMM-Newton spectrum exhibits excess emission below that energy. This excess emission could be from the ionised emitter that was present at that time (Grupe et al 2007;Longinotti et al 2008). The ratio of the difference spectrum (2006FI data -2013 from the high-flux spectrum) fitted with a power law between 2.5 − 10 keV reveals significant changes in the Fe Kα band and below about 2 keV.…”
Section: The Spectral Characteristics In the High-and Low-statementioning
confidence: 93%
“…Holt et al 1980;Reichert et al 1985;Boller et al 2002Boller et al , 2003Immler et al 2003;Tanaka et al 2004;Gallo et al 2004a,b;Pounds et al 2004;Turner et al 2005;Grupe et al 2007, inter alia). previously tested a partial covering model for the 2001 XMM-Newton spectrum of MCG-6-30-15 and concluded that, although such a model provided an acceptable fit, a relativistically-blurred model was superior.…”
Section: The Role Of Absorber Partial Coveringmentioning
confidence: 98%
“…Despite their different shape in the Fe-line energy region, the superposition of different layers of partially-ionised absorbing material could mimic the presence of a broad line component superimposed to the continuum, a feature naturally present in a relativistically-blurred, ionized reflection model (see e.g. Reeves et al 2004;Grupe et al 2007;Petrucci et al 2007 Table 3). …”
Section: The Emission At Energies >3 5 Kevmentioning
confidence: 99%